Transmutation of Emersonian individualism and the American dream in two American novels : the Great Gatsby (1925) by F. Scott Fitzgerald and Henderson the Rain King (1959) by Saul Bellow - Nurul Akmal binti Che Noor Azeman
Individualism in America is an ideology which celebrates self-autonomy. It is a core of American identity and believes that every individual is in charge of his or her own happiness, life and fate. This research critically analyses F. Scott Fitzgerald's The Great Gatsby (1925) and Saul Bellow's Henderson the Rain King (1959) based on Ralph Waldo Emerson's (1803-1882) ideology of individualism. The main focus of this research is to examine the novels' protagonists and how they portray their sense of individualism in comparison to Emerson's. The research aims to explore the transmutation of the ideology in these two novels by thoroughly examining cultural background, moral consciousness of the protagonists as well as their spiritual outlooks on life in texts. The focus of this thesis will mainly revolve around the transmutation of Emersonian individualism, possible causes and how it affects individual spiritual awakening. In this thesis, it was found that both protagonists, Jay Gatsby and Eugene Henderson, display a transmutated version of Emersonian individualism. The transmutation of Emersonian individualism occurred due to cultural shifts in America as the nation enjoyed economic prosperity in the 1920s and 1950s. As a result, both protagonists suffer morally and spiritually because their uptakes of individualism are based on material and physical comfort instead of spirituality. However, unlike Gatsby who is consistently lulled by the promises of his false dreams which comes in the shape of American Dream, Henderson attempts to steer away from the false concept of Emersonian individualism and strives to re-discover its true concept and finally achieve inner peace. There are various limitations found while conducting this research. This is because of the overlapping nature of American individualism which intertwined with its historical, cultural and religious background. Hence, future researchers who are interested in this area of study may explore more impacts of Emersonian individualism to American psyche today by including at least five written works which span between several eras instead of just two.